Eksterminasi Hoaks Melalui “3S” Berbasis al-Qur'an - Faldiansyah, Iqrom; Amantha, Bimma (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2023)
Today, the problem that arises due to the increase in social media users is the number of hoaxes that are widespread around us. Suppressing hoaxes on social media can be categorized as very difficult. Because the phenomenon that occurs in society assumes that hoax is a trivial matter. So that, the spread of hoaxes through social media has become a common thing in everyday life. This paper uses a literature study method to see how solutions can be made at the personal level to deal with hoaxes. The concept offered is "3S" which is based on Qs. Al-Hujurat (49):6. The concept of the idea of "3S" is oriented to the individual ability of social media users to prevent and ward off hoaxes. The concept of the "3S" idea is to be selective in receiving news, searching before sharing, and being aware of the dangers of hoaxes. It is hoped that the implementation of this idea can stop the spread of hoaxes on social media.